2016
DOI: 10.1080/00219266.2016.1177569
|View full text |Cite
|
Sign up to set email alerts
|

Learning genetics through a scientific inquiry game

Abstract: In this paper we discuss an activity through which students learn basic concepts in genetics by taking part in a police investigation game. The activity, which we have called Recal, immerses students in a scientific-based scenario in which they play a role of a scientific assessor. Players have to develop and use scientific reasoning and evidence-based decision-making to solve the given enigmas along the game. The activity aims to improve students' knowledge of genetics and show them how genetic evidence can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
13
0
3
Order By: Relevance
“…The results of the second hypothesis indicated that there is a medium positive correlation between problem-based learning and academic achievements referring to experimental group (r = 0.487), as well as to control group (r = 0.315). The result was consistent with previously reported works, who argued that there is a significant positive relationship between problem-based learning and academic achievement (Grabau and Ma, 2017;Odom and Bell, 2015;Post et al, 2006;Stecker, Fuchs and Fuchs, 2005;Philip et al, 2008;Kitchen et al, 2007;Harris, 2009;Coca, 2012;Mello et al, 2017;Moutinho, Moura and Vasconcelos, 2017;Casanoves, 2017;Andersson and Reimers, 2009). In conclusion the second hypothesis "there is a positive linear correlation between problem-based learning and academic achievements in science" is been supported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the second hypothesis indicated that there is a medium positive correlation between problem-based learning and academic achievements referring to experimental group (r = 0.487), as well as to control group (r = 0.315). The result was consistent with previously reported works, who argued that there is a significant positive relationship between problem-based learning and academic achievement (Grabau and Ma, 2017;Odom and Bell, 2015;Post et al, 2006;Stecker, Fuchs and Fuchs, 2005;Philip et al, 2008;Kitchen et al, 2007;Harris, 2009;Coca, 2012;Mello et al, 2017;Moutinho, Moura and Vasconcelos, 2017;Casanoves, 2017;Andersson and Reimers, 2009). In conclusion the second hypothesis "there is a positive linear correlation between problem-based learning and academic achievements in science" is been supported.…”
Section: Discussionsupporting
confidence: 92%
“…Student-staff partnership and peer-learning as well as model-based learning improved understanding of bioinformatics and its relevance to research, developed a better understanding of the subject, and influenced restructuring students' mental models in addition to the development of meaningful learning to teach the "seismic effects on soils and buildings" (Mello et al, 2017;Moutinho, Moura and Vasconcelos (2017). Casanoves (2017) showed that scientific reasoning and evidence-based decision-making to solve the given enigmas which is learner-centered approach to improve students' knowledge of genetics. Andersson and Reimers (2009) suggested that students' learning outcomes improved student perceptions of computer information systems instructors with information technology certifications positively enhanced their assessment of the instructor effectiveness, teaching methodology, and student engagement.…”
Section: The Problem-based Learning and Academic Achievementsmentioning
confidence: 99%
“…Son muchos los estudios que han abordado este desafío diseñando y probando nuevas actividades de enseñanza y aprendizaje. Casanoves et al (2016) utilizan la metodología educativa del aprendizaje basado en problemas para aprender conceptos básicos de genética mientras resuelven un caso de investigación policial. Solé-Llussà et al (2019) utilizan el aprendizaje basado en el juego, esta metodología incorpora múltiples herramientas y recursos, con el objetivo de que el alumnado aprenda haciendo y se familiarice con la toma de decisiones.…”
Section: Discussionunclassified
“…Molecular genetics, which is thought to be the cornerstone of modern biology (Rotbain, Marbach-Ad & Stavy, 2005;Gericke & Wahlberg, 2013), continues to be one of the problematic topics for students, especially those at the senior high school level (Marbach-Ad & Stavy, 2000;Tsui & Treagust, 2010;Thörne & Gericke, 2014;Kılıç & Sağlam, 2014;Aivelo & Uitto, 2015;Casanoves, Salvadó, González, Valls, & Novo, 2017). This has been reported in a myriad of studies which showed students at the senior high school level demonstrate a poor understanding of fundamental issues related to molecular genetics (Knippels, Waarlo, & Boersma, 2005;Kılıç & Sağlam, 2014;Solé-Llussà, Casanoves, Salvadó, Garcia-Vallve, Valls, & Novo, 2019).…”
Section: Introductionmentioning
confidence: 99%